2018
DOI: 10.1021/acsanm.8b00709
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Graphene Oxide Membrane in Forward Osmosis: Molecular Insights

Abstract: We investigate the performance of layered graphene oxide (GO) membrane in forward osmosis (FO) process for seawater desalination via nonequilibrium molecular dynamics (MD) simulations. A 0.56 M NaCl solution is used as the feed solution and a mixture of 1.0 M MgCl2 and 0.05 M Al2(SO4)3 solution is used as a draw solution. The effect of internal structure of the layered GO membrane on its performance as a FO membrane is investigated by considering three different membrane configurations which differ in their po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…Recent atomistic simulation studies also support this notion. [36][37][38] The performance of a layered GO membrane also depends on the size of the constituent GO nanosheets. With the increase in the size of the GO nanosheets the water permeability of the layered GO membrane decreases and its salt rejection increases.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent atomistic simulation studies also support this notion. [36][37][38] The performance of a layered GO membrane also depends on the size of the constituent GO nanosheets. With the increase in the size of the GO nanosheets the water permeability of the layered GO membrane decreases and its salt rejection increases.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in the size of the GO nanosheets the water permeability of the layered GO membrane decreases and its salt rejection increases. 36,37,39 Very recently it was reported that with the inclusion of non-idealities in layered GO membranes, there is substantial reduction in the difference in water permeability of the size-differentiated GO laminates by the experimental and simulation (using nite element analysis) study of Saraswat et al 30 The two major factors (or non-idealities) contributing to this scenario are Pinhole defects on the constituent GO nanosheets: pinhole defects located on the GO nanosheets can play a pivotal role in water permeation through layered GO membranes by providing a shorter route for trans-sheet ow. 30,32,40 Imperfect stacking of the GO nanosheets: the ideal (or perfect) lamellar stacking of GO nanosheets in layered GO membranes may not be possible in practical scenarios.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations